Implementing Universal Design for Learning in Islamic Education: Strategic Management for Children with Special Needs - Ofiani, Oktawini; Harmi, Hendra; Wanto, Deri (JURNAL AL-TANZIM, 2025)
This study aims to analyze the management strategies of Universal Design for Learning (UDL) applied in Islamic education to support children with special needs in schools. This research uses a qualitative, case-study approach. Data was collected through interviews, observations, and documentation. Data analysis is carried out using an interactive model comprising three main stages: data reduction, data presentation, and conclusion. The results showed that PAI teachers implemented the principles of UDL by utilizing various media and approaches, such as images, videos, Braille Qur'an, and sign language, to ensure that all students, including those with sensory, motor, and cognitive barriers, could access the material effectively. In addition, teachers provide flexibility in the learning pace and set learning goals tailored to individual students' abilities. The implication of this study is the importance of teacher capacity building in the use of adaptive media and educational technology, as well as continuous training to support the optimal implementation of UDL. This research also contributes to enriching the understanding of the application of UDL in religious education for children with special needs (ABK), thereby improving inclusivity and the quality of learning for students with diverse needs.